Comparison of Counterpressure with Birthball to Fear of Facing Labor - Neng Rani Fitriyani; Feva Tridiyawati (Proceedings of the International Conference on Nursing and Health Sciences, 2023)
Fear of childbirth' (FOC) is defined as "intense anxiety that has interfered with the process, function and well-being during childbirth. This fear is caused by pain inflicted during labor, so finding ways to reduce pain will automatically decrease fear in labor. Nonpharmacological methods that can be used to reduce labor pain are birth ball therapy and counter pressure. The purpose of this study was to conduct a scientific analysis of the effectiveness of birth ball and counterpressure against reducing fear in the face of childbirth. This research is designed experimental quasy. This location is at the Bunda Aya Kragilan clinic, Serang-Banten in May-June 2023. In this study were 30 maternity mothers. The analysis used is an independent t test. The results of the independent t test obtained a Sig.2-tailed value of 0.002 for the birth ball and the results of the independent t test obtained a Sig.2-tailed value of 0.024. Birt balls and counterpressure are effective in reducing the fear of childbirth